Carbon Footprint and Techno-economic Analysis to Decarbonize the Production of Linerboard via Fuel Switching in the Lime Kiln and Boiler: Development of a Marginal Abatement Cost Curve - Rodrigo Buitrago-Tello; Richard A. Venditti; Hasan Jameel; Peter W. Hart; Ashok Ghosh (BioResources, 2025)
The US Pulp and Paper (P&P) industry heavily relies on fossil sources, with lime kiln operations posing a significant challenge for achieving zero on-site fossil emissions. This study assesses the greenhouse gas (GHG) reduction potential and costs associated with alternative fuels in lime kiln operations for linerboard production. Various options, including bio-based fuels including pulverized biomass, gasification of biomass, crude tall oil, bio-methanol, and traditional fuels such as fuel oil and petcoke, were analyzed through detailed process simulations and Life Cycle Assessment. Results indicate that per ton of product, 2,789 kg of CO2-eq is emitted, with 69% being biogenic CO2 and 31% fossil CO2-eq. Notably, replacing the natural gas boiler with a biomass boiler reduces Global Warming Potential (GWP) by 41%, while switching lime kiln fuel to biofuels achieves a 5.5% reduction. Combining a biomass boiler with pulverized biomass fuel use in the lime kiln yields a substantial 93.1% reduction in Scope 1 and 2 emissions, at a cost of $76/ton of CO2-eq avoided.